COMPOSITION OF THE ESSENTIAL OIL FROM MIMOSA PUDICA LINN. - TK, VISMAYAVISWAN; J, DHARANI; R, SRIPATHI; S, RAVI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: To determine the composition of the essential oil obtained from Mimosa pudicaÂ L. (Mimosaceae) Â Methods: The essential oilÂ Â of M. pudica was obtained by hydro distillation using a Clevenger apparatus and the chemical composition was determined by GC-MS analysis. Â Results: About 23 compounds were identified from the essential oil which constitutes about 98.92 % of the oil. Among the compounds identified phthalic acid dioctyl ester (27.76 %), Î±-Linolenic acid (20.34 %), Cinnamaldehyde (16.24 %) are the major compounds.Â Î±-Linolenic acid is an n-3 fatty acid. Â Conclusion: Î±-Linolenic acid is one of the essential fatty acids, which is necessary for health and cannot be produced within the human body.Â Mimosa pudicaÂ L. (Mimosaceae) appears to be a promising herb to undergo a wide exploration